Low light reduces saffron corm yield by inhibiting starch synthesis - Yang, Weijing; Li, Xin; Chang, Fei; Qiu, Xue; Huang, Xulong; Feng, Zhan; Yan, Jie; Wu, Qinghua; Wen, Feiyan; Pei, Jin; Zhou, Tao (Frontiers in Plant Science, 2025)
The mechanisms by which low light modulates source-sink dynamics, affecting starch synthesis and formation of underground storage organs in geophyte, remain unclear. In this study, a two-year field experiment was conducted under natural light (NL) and low light (LL, 50% of NL intensity) conditions. LL resulted in a 23.66% and 21.23% reduction in corm yield in 2023 and 2024, respectively. Saffron plants under LL had larger, longer leaves with a higher proportion of dry weight (DW) compared to those under NL. Despite the marked inhibition of photosynthetic capacity, initial DW, sucrose and glucose concentrations in leaves were comparable to those under NL. Carbohydrate analysis revealed that starch concentration in the mother corms under LL decreased by 18.00% relative to NL, while sucrose and glucose concentrations increased by 28.44% and 68.44%, respectively. At the corm expansion stage, sucrose concentration in leaves and daughter corms under LL conditions was 17.32% and 54.08% higher than under NL, but glucose and starch concentrations in daughter corms were 22.08% and 10.22% lower, respectively. Additionally, the activity of invertase (INV), sucrose synthase in the decomposition direction (SUS) and ADP-glucose pyrophosphorylase (AGPase) in daughter corms were reduced under LL. LL also affected phytohormones concentrations, with increased levels of indole-3-acetic acid (IAA) and gibberellin (GA1) in LL leaves and daughter corms, and decreased abscisic acid (ABA) levels. Transcriptome and quantitative PCR analyses showed that LL upregulated the expression of genes involved in glycolysis and the tricarboxylic acid cycle in leaves, while downregulating CsSUS, CsINV1, CsAGPS1, CsZEP, and CsNCED, which are key to sucrose hydrolysis, starch synthesis, and ABA biosynthesis. Exogenous GA3 application further inhibited SUS, INV and AGPase activities in daughter corms, indicating that high GA concentrations impair carbohydrate metabolism in these organs. In conclusion, LL decreases saffron corm yield by promoting the allocation of reserves from mother corms to leaves at the seedling stage. By the period of the daughter corms enlargement, elevated GA1 and IAA levels and reduced ABA concentration promote leaf growth while inhibiting carbohydrate metabolism in daughter corms, thereby reducing sucrose transport from leaves to daughter corms and suppressing corm yield formation.